2015
DOI: 10.1016/j.physbeh.2015.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Wheel running decreases palatable diet preference in Sprague–Dawley rats

Abstract: Physical activity has beneficial effects on not only improving some disease conditions but also by preventing the development of multiple disorders. Experiments in this study examined the effects of wheel running on intakes of chow and palatable diet e.g. high fat (HF) or high sucrose (HS) diet in male and female Sprague Dawley rats. Experiment 1 demonstrated that acute wheel running results in robust HF or HS diet avoidance in male rats. Although female rats with running wheel access initially showed complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
4
17
0
5
Order By: Relevance
“…Results of experiment 1 replicated our previous results that wheel running induces reduced intake of a novel HF diet (29) and demonstrated that plasma corticosterone levels were significantly increased and positively correlated with wheel-running activity during the two-diet-choice feeding regimen. The results are consistent with our hypothesis that elevation of circulating corticosterone may be involved in wheel-runningassociated reduction in HF diet intake/preference.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Results of experiment 1 replicated our previous results that wheel running induces reduced intake of a novel HF diet (29) and demonstrated that plasma corticosterone levels were significantly increased and positively correlated with wheel-running activity during the two-diet-choice feeding regimen. The results are consistent with our hypothesis that elevation of circulating corticosterone may be involved in wheel-runningassociated reduction in HF diet intake/preference.…”
Section: Discussionsupporting
confidence: 82%
“…Wheel running immediately reduces intake of and preference for a HF diet regardless of its familiarity (23,29). Results of experiment 1 replicated our previous results that wheel running induces reduced intake of a novel HF diet (29) and demonstrated that plasma corticosterone levels were significantly increased and positively correlated with wheel-running activity during the two-diet-choice feeding regimen.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations